IMPROVING NUMERACY LITERACY SKILLS OF ELEMENTARY SCHOOL STUDENTS THROUGH THE KAMPUS MENGAJAR (KAMPUS MENGAJAR) PROGRAM POLICY - Nurul Fatonah; Johar Permana; Ernawulan Syaodih (Universitas Majalengka, 2023)
Literacy and numeracy abilities are determining factors for individual success in learning. Currently, literacy and numeracy skills are the main subjects in the independent curriculum. As one of the programs of the independent curriculum in tertiary institutions, the kampus mengajar is intended to serve the purpose of increasing students' literacy and numeracy skills. This study aims to describe the results of research on improving literacy and numeracy skills in elementary schools. This research uses a qualitative approach. Data was collected through interviews and questionnaires. The object of this research is schools that run kampus mengajar programs in Garut Regency. The data were then analyzed using qualitative methods. The results of this study indicate that the kampus mengajar program has contribution in increasing students' literacy and numeracy in elementary schools, especially 3T schools. The kampus mengajar program contributes a lot to activities both in learning and activities outside the classroom. This is very possible for students to have good literacy skills. This is due to the existence of learning innovations offered by students in the target schools. Kemampuan literasi dan numerasi menjadi faktor penentu keberhasilan individu dalam belajar. Saat ini kemampuan literasi dan numerasi menjadi pembelajaran pokok di kurikulum merdeka. Sebagai salah satu program dari kurikulum merdeka di perguruan tinggi, kampus mengajar dimaksudkan untuk melakukan pengabdian pada peningkatan kemampuan literasi dan numerasi siswa. Kajian ini bertujuan untuk mendeskripsikan hasil penelitian tentang peningkatan kemampuan literasi dan numerasi di sekolah dasar. Penelitian menggunakan pendekatan kualitatif dengan metode studi fenomenologi. Data diambil melalui wawancara dan angket. Objek penelitian ini yaitu sekolah-sekolah yang menjalankan program kampus mengajar di Kabupaten Garut. Data kemudian dianalisis dengan metode kualitatif. Hasil penelitian ini menunjukan bahwa program kampus mengajar memiliki kontribusi dalam meningkatkan literasi dan numerasi siswa di sekolah dasar terutama sekolah 3T. Program kampus mengajar memberikan banyak kontribusi kegiatan baik dalam pembelajaran ataupun kegiatan di luar kelas. Hal ini sangat memungkin siswa memiliki kemampuan literasi yang baik. Ini dikarenakan adanya inovasi pembelajaran yang ditawarkan oleh mahasiswa di sekolah sasaran.